Stepwise degradation of membrane sphingomyelin by corynebacterial phospholipases. - Bernheimer, A W (1980)
The mechanism of in vitro synergistic lysis of sheep erythrocytes by Corynebacterium ovis and Corynebacterium equi was investigated. Hemolysis required (i) the action of phospholipase D from C. ovis, (ii) the action of an extracellular protein of C. equi, and (iii) Mg2+. Maximum lysis required imposition on the system of a fourth condition (step iv), such as chilling. Steps i, ii, and iv occur sequentially and in that order. Mg2+ functions in steps i and ii. The extracellular protein C. equi was purified to homogeneity and found to be a phospholipase C capable of hydrolyzing ceramide phosphate, phosphatidic acid, and all of the isolated major phospholipids of mammalian erythrocyte membranes. The principal features of the synergistic hemolytic system could be reproduced in experiments involving liposomes containing either sphingomyelin or ceramide phosphate and trapped [14C]glucose. We inferred that sphingomyelin of sheep erythrocytes is first converted to ceramide phosphate by C. ovis phospholipase D. On the basis of results with liposomes, we propose that the ceramide phosphate is then converted to ceramide by C. equi phospholipase C. We believe that the resulting in situ ceramide then undergoes dislocation by chilling and perhaps also by virtue of an affinity between ceramide and C. equi phospholipase C. The dislocation of ceramide presumably disorganizes the lipid bilayer sufficiently to result in cell lysis.